2008
DOI: 10.1080/10826080802238009
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Analysis of Stressful Life Events, Smoking Behaviors, and Gender Differences in a Multicultural Sample of Adolescents

Abstract: Many studies have addressed the associations between stressful life events and adolescent smoking. Few studies, however, have examined gender differences, specifically with multicultural samples. This longitudinal study examines the relationship between 6 stress subscales and smoking behaviors 716 multicultural U.S. adolescents living in the greater Los Angeles area in 2000-2001. At baseline the ethnic break-down of the sample was 63% Latino and 26% Asian/PI and 70% were 11 years of age. Negative personal even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
1
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 71 publications
4
22
1
6
Order By: Relevance
“…The finding that nonwhite ethnicity, lower education, and younger age were associated with an increased number of life events is in accord with a recent review of life events in relation to sociodemographics (50). Similarly, in prior research, those experiencing stressful events are more likely to smoke and have higher BMI, consistent with our findings (51)(52)(53). The positive association between life events and STD diagnosis may suggest a group with a history of high-risk behaviors (i.e., unprotected intercourse), although we did not observe an association between alcohol intake and illicit drug use in the last week.…”
Section: Discussionsupporting
confidence: 94%
“…The finding that nonwhite ethnicity, lower education, and younger age were associated with an increased number of life events is in accord with a recent review of life events in relation to sociodemographics (50). Similarly, in prior research, those experiencing stressful events are more likely to smoke and have higher BMI, consistent with our findings (51)(52)(53). The positive association between life events and STD diagnosis may suggest a group with a history of high-risk behaviors (i.e., unprotected intercourse), although we did not observe an association between alcohol intake and illicit drug use in the last week.…”
Section: Discussionsupporting
confidence: 94%
“…There is an abundant literature investigating the relation between stressful life circumstances and behaviors such as smoking (Aronson et al, 2008, Booker et al, 2007, Booker et al, 2008) and drinking (Castillo et al, 2008, Jennison, 1992, Windle and Windle, 1996). Several studies have reported an association between self-reported discrimination (which can be conceptualized as a stressor) and smoking in blacks (Landrine and Klonoff, 2000, Guthrie et al, 2002, Bennett et al, 2005, Resnicow et al, 1999, Kwate et al, 2003, Borrell et al, 2007, Krieger et al, 2005, Landrine et al, 2006), whites (Borrell et al, 2007, Krieger et al, 2005, Landrine et al, 2006), Hispanics (Landrine et al, 2006, Krieger et al, 2005) and Asians (Landrine et al, 2006, Chae et al, 2008a) in the U.S. and in other ethnic groups elsewhere (Harris et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…For example, adolescent girls who reported more daily hassles (an index of stress level) were more likely to report having ever smoked (Guthrie et al, 2001). Also, stress appears to be related to the intention to smoke (Booker et al 2004); and more recent longitudinal analyses have extended this finding to show that developmentally early stress is associated with lifetime smoking (Booker et al, 2008). …”
Section: Introductionmentioning
confidence: 98%